The use of retinoids in the treatment of skin lesions and prevention of signs of skin aging - a systematic review - Zapała, Magdalena; Hunek, Adrian; Kaziród, Karolina; Chmielarz, Karolina; Wiśniewska-Skomra, Joanna; Tylutka, Kinga; Hapon, Anna; Dadziak, Mikołaj (Journal of Education, Health and Sport, 2023)
Retinoids are a group of substances that include vitamin A and its natural and synthetic derivatives. They are used in the treatment of various skin diseases, such as: rosacea, acne vulgaris, psoriasis. In addition, recently there is a lot of information about the action of preventing photoaging. Oral retinoids have been proven to be the most effective treatment for acne of various severity available today. Through their comprehensive action, affecting the four main factors associated with the pathogenesis of acne, they significantly reduce skin changes. Externally applied retinoids regulate the renewal of epidermal cells, stimulate the production of collagen fibers, increase the production of elastin, and lead to an increase in the number and activity of fibroblasts. Therefore, more and more people are using preparations containing retinoids to prevent skin aging. It has been proven that this procedure leads to shallower wrinkles and slows down the appearance of new ones, and evens out the skin tone. Retinoids are effective substances, but their use is associated with the risk of various side effects, the most common of which are: skin irritation, photosensitisation, headaches, muscle and joint pain, and teratogenicity.